An electronic health record-based strategy to recruit for a Patient Advisory Council for Research: Implications for inclusion. Issue 1 (25th February 2020) - Bougrab, Nassira; Li, Dadong; Trachtman, Howard; Sherman, Scott; Thornton, Rachel; Langford, Aisha T.
Abstract: In 2017, the NYU Clinical and Translational Science Institute's Recruitment and Retention Unit created a Patient Advisory Council for Research (PACR) to provide feedback on clinical trials and health research studies. We collaborated with our clinical research informatics team to generate a random sample of patients, based on the International Classification of Diseases, Tenth Revision codes and demographic factors, for invitation via the patient portal. This approach yielded in a group that was diverse with regard to age, race/ethnicity, sex, and health conditions. This report highlights the benefits and limitations of using an electronic health record-based strategy to identify and recruit members for a PACR.